Internal regulation in compressible turbulent shear layers. (26th November 2020) - Matsuno, K.; Lele, S. K.
Abstract: Abstract : High-resolution simulations of temporally evolving mixing layers, for convective Mach numbers ranging from M_c=0.2 to M_c=2.0 with density ratios s=1 and s=7, are analysed to characterize compressibility effects on the structure and evolution of turbulence in this compressible flow. Published experimental results are used to validate simulation results. Examination of the turbulence scales in the present data suggests an internal regulation mechanism. Correlated eddying motions were found to be in support of a 'sonic eddy hypothesis'. Eddy scales in all spatial directions are found to be a progressively smaller fraction of the overall mixing-layer thickness with increasing M_c, forming independent layers of eddying motions at high M_c . These reduced spatial scales serve to reduce the effective velocity scale for turbulent motions, suppressed Reynolds stresses, turbulent kinetic energy (TKE) production and dissipation, and the mixing-layer thickness growth rate.